Global Proteomic Analysis of Lysine Crotonylation in the Plant Pathogen Botrytis cinerea - Zhang, Ning; Yang, Zhenzhou; Liang, Wenxing; Liu, Mengjie (Frontiers in Microbiology, 2020)
Lysine crotonylation (Kcr), a recently discovered post-translational modification, plays a key role in the regulation of diverse cellular processes. Botrytis cinerea is a destructive necrotrophic fungal pathogen distributed worldwide with broad ranging hosts. However, the functions of Kcr are unknown in B. cinerea or any other plant fungal pathogens. Here, we comprehensively evaluated the crotonylation proteome of B. cinerea and identified 3967 Kcr sites in 1041 proteins, which contained 9 types of modification motifs. Our results show that although the crotonylation was largely conserved, different organisms contained distinct crotonylated proteins with unique functions. Bioinformatics analysis demonstrated that the majority of crotonylated proteins were distributed in cytoplasm (35%), mitochondria (26%), and nucleus (22%). The identified proteins were found to be involved in various metabolic and cellular processes, such as cytoplasmic translation and structural constituent of ribosome. Particularly, 26 crotonylated proteins participated in the pathogenicity of B. cinerea, suggesting a significant role for Kcr in this process. Protein interaction network analysis demonstrated that many protein interactions are regulated by crotonylation. Furthermore, our results show that different nutritional conditions had a significant influence on the Kcr levels of B. cinerea. These data represent the first report of the crotonylome of B. cinerea and provide a good foundation for further explorations of the role of Kcr in plant fungal pathogens.